If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + -5) = 81 Reorder the terms: 3(-5 + 2x) = 81 (-5 * 3 + 2x * 3) = 81 (-15 + 6x) = 81 Solving -15 + 6x = 81 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + 6x = 81 + 15 Combine like terms: -15 + 15 = 0 0 + 6x = 81 + 15 6x = 81 + 15 Combine like terms: 81 + 15 = 96 6x = 96 Divide each side by '6'. x = 16 Simplifying x = 16
| 5x+87=54 | | -7n+8=15 | | 2x-10=2x+20 | | z-16=-15 | | 5z-2=4z | | 8n-32+8n=-128 | | 2+16c=52 | | 3.6(2p+4)=3(2-3p) | | 6-3a=10a | | (k-6)-2=10 | | y=2x^2-3x-4 | | xcube=64 | | 1+8x+2x=2+6x+2-7 | | 18a^2-15a-63=0 | | -4(3x+4)=-88 | | 6a+3=4a-1 | | 5w-13-3w=15 | | 120=-6(4-6n) | | ln(2-3x)=1 | | 1=3w-6 | | -10=-4p-6p | | 57t-64-(7-20t)= | | 20y+30x+2+30y-30x= | | 4n-2=-6+5n | | 2c+16=52 | | -8x+24=-68 | | 11+100x-11+30x= | | 18=13-(3+4x) | | (3x^2+26x-32)=0 | | x*x*x-4x=0 | | 14=-4(5+5a)+6(8+a) | | 6x-5x=x+1 |